First occurrence of Panthera atrox (Felidae, Pantherinae) in the Mexican state of Hidalgo and a review of the record of felids from the Pleistocene of Mexico - V. M. Bravo-Cuevas; J. Priego-Vargas; M. Á. Cabral-Perdomo; M. A. Pineda Maldonado (Fossil Record, 2016)
Panthera atrox was a common large-sized cat in North America during the late Pleistocene. An isolated lower canine and a fifth metacarpal bone referable to this species were recovered from fluvial Quaternary deposits that outcrop in southeastern Hidalgo, central Mexico. Associated fossil material belonging to Bison indicates a Rancholabrean North American Land Mammal Age; the age assignment is corroborated by the presence of P. atrox. A comparative study with selected specimens of Panthera and Smilodon indicates that the Hidalgoan sample shares the following diagnostic features with P. atrox: a large, robust, and non-strongly curved lower canine; a large and relatively slender fifth metacarpal with a well-developed projection on the palmar side at the proximal end, narrow articulating surface for the unciform; a narrow notch on the articulating surface for the fourth metacarpal; and a diaphysis that at the middle is oval in cross section. The record supplements the evidence of P. atrox in central Mexico and represents the first reported occurrence of this cat species in the state of Hidalgo. By the same token, the known geographic distribution of P. atrox in the Mexican territory suggests that it was relatively common in temperate areas of central Mexico between 19 and 24° N at an altitudinal range from 1500 to 2250 m a.s.l. The large size (mean body mass of 300 kg) and hypercarnivorous adaptations of the American lion suggest it was the top predator of the mammalian community recorded at southeastern Hidalgo, displacing other members of the carnivore guild at the mesopredator level, such as the dire wolf (Canis dirus ), which has been also reported in the area. The high diversity of large herbivores recorded at southeastern Hidalgo, which in turn could represent potential prey of P. atrox, suggests that some areas that now are part of central Mexico were suitable hunting sites for this large-sized cat. A review of the Pleistocene record of Felidae from Mexico revealed that it encompasses 87.5 and 73.3 % of generic and specific diversity known for North America, respectively, including seven genera (Felis, Miracinonyx, Panthera, Puma, Lynx, Leopardus, and Smilodon) and 11 species (Felis rexroadensis, Miracinonyx inexpectatus, Panthera atrox, Panthera onca, Puma concolor, Puma yagouaroundi, Lynx rufus, Leopardus pardalis, Leopardus wiedii, Smilodon fatalis, and Smilodon gracilis). The majority of these taxa have been reported from numerous late Pleistocene localities; in particular, Panthera atrox was relatively common and widely distributed across the Mexican territory.